Africana Congress 2000 - Africana Studies Committee (2000)
Africana Congress 2000 was held at McGill University from February 4" to February 6” 2000. Organized by the Africana Studies Committee and the Black Student Network, and sponsored in large part by Canadian Heritage, the event served to celebrate and critically re-evaluate 30 years of Africana Studies at McGill University. The Congress marked a major turning point in the struggle to maintain and promote Africana Studies at McGill University. It was first conceived two years earlier, when the Africana Studies Committee (ASC) drafted its 1998 Development Plan, a document that charted ASC’s 20-year vision for the potential expansion of the program. The plan was divided into four phases, the final one being the establishment of an Africana Studies Centre. In the interim, the Congress was conceived and proposed as a way of mobilizing as much support for the initiative as possible. The Congress was also conceived as a forum that would welcome input and would generate discussion about how to achieve our goals. ASC without engaging in acknowledged that it could not achieve these ambitious, though not unrealistic, goals with genuine consultations with the wider community.